PERFORMANCE OF VORTEX TURBINES IN ULTRA-LOW-HEAD HYDROELECTRIC POWER PLANTS: A NUMERICAL STUDY - Firdaus Asyhar; M. Furkon Hakim; Sunaryo (Clean Energy and Smart Technology, 2025)
The performance of vortex turbines in ultra-low-head hydropower plants is crucial for harnessing energy in irrigation channels and small rivers. Therefore, an optimal design is needed to maximize the conversion of flow energy into electrical power. This study aims to evaluate and determine the best-performing configuration of ultra-low-head vortex turbines. The method used is Computational Fluid Dynamics (CFD) simulations employing the k-ω Standard turbulence model, with variations in the number of blades (3, 5, and 7) and a fixed blade angle of 15°. The results show that the 7-blade configuration with a 15° angle provides superior performance, generating 3.90 W of power, reducing NPSH by 2%, and increasing force by 6%, with a force value of 52.65 N. The implications of these findings suggest that the 7-blade–15° configuration is a suitable design reference for optimizing ultra-low-head vortex turbines in micro-scale hydroelectric power plants, supporting the utilization of renewable energy in irrigation networks and rural areas.